Taxonomical status of endemic freshwater ichthyofauna of Sulawesi - Renny Kurnia Hadiaty (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2018)
The freshwaters of Sulawesi are the habitat of numerous endemic Indonesian ichthyofauna that are not found anywhere else in the world. About 68 endemic fish species described from the Sulawesi’s freshwaters, it consisted of seven fami-lia of four order. The seven familia are Adrianichthyiidae (19 spesies, two genera), Telmatherinidae (16 spesies four gen), Zenarchopteridae (15 spesies, three gen), Gobiidae (14 spesies., empat gen), Anguillidae (one spesies, one gen), Eleotridae (two spesies, two gen), Terapontidae (one spesies, one gen). Most of the Sulawesi’s endemic ichthyofauna inhabit in lakes (45 spp., about 66.2%), 23 spp. lives in the rivers. The Sulawesi’s first species was Glossogobius cele-bius described by Valenciennes in 1837, the type spesimen deposited in Paris Museum. Eight species described in 19 century, up to the year of Indonesian independence 29 spesies described, after that 39 spesies of endemic ichthyofauna described from Sulawesi’ freshwater. The earlier description the type specimen deposited in the foreign museums, but in 1990 Dr. Maurice Kottelat pioneered to deposited the type specimen in Museum Zoologicum Bogoriense (MZB), Zoologi Division of Research Center for Biology. So far, the type specimens of Sulawesi freshwater ichthyofauna deposited in 27 museums of 11 countries in the world, the most museums were in United Stated of America (8 mu-seums), Germany (6 museums), Schwitzerland (3 museums), Australia and Netherlands (2 museums), while the others (Austria, Japan, Singapore, United Kingdom and Indonesia) each country with one museums respectively. Abstrak Perairan tawar Pulau Sulawesi merupakan habitat beragam iktiofauna endemik Indonesia yang tidak dijumpai di bagian manapun di dunia ini. Dari perairan tawar pulau ini telah dideskripsi 68 spesies ikan endemik dari tujuh familia, tergo-long dalam empat ordo. Ke tujuh familia tersebut adalah Adrianichthyiidae (19 spesies, dua genera), Telmatherinidae (16 spesies, empat genera), Zenarchopteridae (15 spesies, tiga genera), Gobiidae (14 spesies, empat genera), Anguilli-dae (satu spesies, satu genus), Eleotridae dua spesies, dua genera), dan Terapontidae (satu spesies, satu genus). Seba-gian besar spesies endemik di P. Sulawesi hidup di perairan danau (45 spesies atau 66,2%), 23 spesies hidup di perairan sungai. Spesies pertama yang dideskripsi dari P. Sulawesi adalah Glossogobius celebius oleh Valenciennes tahun 1837, spesimen tipenya disimpan di Museum Paris. Delapan spesies ditemukan pada abad 19, sampai sebelum kemerdekaan Indonesia telah ditemukan 29 spesies, setelah merdeka ditemukan 39 spesies di P. Sulawesi. Di awal penemuan spesies baru, spesimen tipe disimpan di museum luar negeri, namun sejak tahun 1990 dipelopori oleh Dr. Maurice Kottelat spesimen tipe disimpan di Museum Zoologicum Bogoriense (MZB), Bidang Zoologi, Pusat Penelitian Biologi. Sampai saat ini spesimen tipe iktiofauna dari P. Sulawesi disimpan di 27 museum dari 11 negara di dunia, terbanyak di Ame-rika (8), Jerman (6), Swiss (3), Australia, dan Belanda (2), sedangkan di Austria, Jepang, Perancis, Singapura, Inggris, dan Indonesia masing-masing satu museum.